Comprehensive metabolite analysis of wheat dough in a continuous heating process. (March 2022) - Cheng, Kunya; Wang, Binchen; Xiao, Lin; Bao, Yuxiang; Xu, Xianbing; Zhang, Sufang; Liu, Zhaofang; Dong, Liang
Graphical abstract: Comprehensive metabolite analysis was performed by GC/MS during wheat dough heating. Thirty-five volatile compounds and sixty-four non-volatile compounds are identified. PCA results demonstrated that metabolic changes were a time-dependent process during heating, and most volatile and non-volatile polar metabolites contributed the heating time-driven changes. Highlights: Comprehensive metabolite analysis was performed by GC/MS during wheat dough heating. Thirty-five volatile compounds and sixty-four non-volatile compounds are identified. PCA results demonstrate metabolic changes is a time-dependent process during heating. Most volatile and non-volatile polar metabolites contributed the heating time-driven changes. Abstract: Comprehensive metabolite analysis was carried out by gas chromatography combined with mass spectrometry to investigate the time-dependent metabolic changes during wheat dough heating. Thirty-five volatile metabolites comprising alcohols, ketones, aldehydes, aromatic compounds, furans, acids and esters were identified. Sixty-four non-volatile metabolites, which covered a broad spectrum of polar and non-polar constituents, were also identified and quantified. Results showed that the content of most volatile metabolites increased during heating. Meanwhile, the levels of non-volatile polar metabolites, such as sugar and amino acid, increased and the levels of non-volatile non-polar metabolites decreased or remained constant, including fatty acid methyl ester and free fatty acids. PCA results demonstrated that metabolic changes could be reflected by time-dependent shifts in the PCA loading scores during heating. Analysis of the loadings further showed that most volatile metabolites and non-volatile polar metabolites were the major contributors of the heating time-driven changes during heating. Furthermore, lipid oxidation mainly occurred in the residues of oleic acid and linoleic acid of triglycerides.